BLOCKCHAIN IMPLEMENTATION IN MILITARY LOGISTICS AND COMMUNICATION SYSTEMS: Rekam Siber - Yovi Retmawan (Jurnal Telkommil, 2025)
The goal of this research is to create and assess a blockchain-based prototype system for military use, particularly in secure communications and logistical monitoring. An Ethereum Testnet smart contract-based secure communications system that enforces stringent access control for message transmission and reception, as well as a Hyperledger Fabric-based logistics tracking system with a permissioned blockchain to guarantee transaction integrity, were the two primary systems that were successfully deployed. According to test results, the logistics system may preserve data integrity by using the SHA-256 hashing algorithm, which records every transaction forever and irrevocably. Only authorized users are able to send and read messages thanks to the smart contract-based communications system's effective defense against unwanted access. The necessity for optimization in real-time applications was highlighted by performance studies that also showed issues with latency as the number of transactions rises. Overall, this study shows that implementing blockchain technology in military systems can enhance data security, dependability, and transparency; nevertheless, scalability and interaction with current military infrastructure require more investigation.